2012
DOI: 10.1051/0004-6361/201219818
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the interstellar medium of the starburst low-metallicity galaxy Haro 11: a multi-phase model of the infrared emission

Abstract: Context. The low-metallicity interstellar medium (ISM) is profoundly different from that of normal systems, being clumpy with low dust abundance and little CO-traced molecular gas. Yet many dwarf galaxies in the nearby universe are actively forming stars. As the complex ISM phases are spatially mixed with each other, detailed modeling is needed to understand the gas emission and subsequent composition and structure of the ISM. Aims. Our goal is to describe the multi-phase ISM of the infrared bright low-metalli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(146 citation statements)
references
References 116 publications
7
138
1
Order By: Relevance
“…Instead, we replace the stellar component by a black body and impose a temperature T ≥ 1000 K. We obtain a best-fit temperature T = 30 000 K, corresponding to a maximum of the black-body emission around 0.1 µm in the UV, a sign of a young stellar population. This is consistent with the results of Adamo et al (2010) who found a maximum in the cluster formation history ∼3.5 Myr ago, and with the UV part of the SED presented in Cormier et al (2012). -HS 0822+3542 -The observed PACS upper limits at 70 and 100 µm are not consistent with the rest of the MIR to FIR photometry (see Fig.…”
Section: A2 Spiresupporting
confidence: 89%
“…Instead, we replace the stellar component by a black body and impose a temperature T ≥ 1000 K. We obtain a best-fit temperature T = 30 000 K, corresponding to a maximum of the black-body emission around 0.1 µm in the UV, a sign of a young stellar population. This is consistent with the results of Adamo et al (2010) who found a maximum in the cluster formation history ∼3.5 Myr ago, and with the UV part of the SED presented in Cormier et al (2012). -HS 0822+3542 -The observed PACS upper limits at 70 and 100 µm are not consistent with the rest of the MIR to FIR photometry (see Fig.…”
Section: A2 Spiresupporting
confidence: 89%
“…The gas becomes optically thick for LyC photons only in the western and eastern outer regions of the galaxy. This pattern mimics the behavior of a giant H ii region, as found for similar galaxies (Haro 11, Cormier et al 2012), and confirms the existence of an in-out ionizing front that modifies the interstellar medium (ISM) states of the galaxy. Several cones of highly ionized gas expanding all the way into the galaxy halo are visible.…”
Section: Ionization Parametersupporting
confidence: 84%
“…In our Milky Way, dense PDRs and CO-dark H 2 gas is responsible for about ∼ 55% of the total [C II] emission, while the diffuse ionized gas and diffuse neutral gas contribute ∼ 20% and 25%, respectively (Pineda et al 2014). Cormier et al (2012) used CLOUDY to model the ISM of the nearby (z ∼ 0.021) starburst galaxy Haro 11, which has a metallicity (∼ 0.3 Z ) and a SFR (∼ 22 M yr −1 ) matching that of our simulations, and found that 10 % of the [C II] luminosity comes from dense PDRs and about 50 % from the diffuse ionized medium.…”
Section: Ism Phases and [C Ii]mentioning
confidence: 99%
“…Galaxy-scale simulations have been developed that attempt to account for the observations of the above finestructure lines, in particular, how their emissions are linked to the ISM phases and to global galaxy properties, such as metallicity, star formation efficiency, ionization parameter, dust mass fraction, compactness and phase filling factors (e.g., Cormier et al 2012;Vallini et al 2013;Olsen et al 2015;Accurso et al 2017;Katz et al 2017). By combining codes of stellar population synthesis, radiative transfer, photoionization, and astrochemistry into simulations of starburst regions, Accurso et al (2017) found that the increases in the specific star formation rate of a galaxy leads to a decrease in the fraction of the [C II] emission coming from the molecular gas phase, due to stronger UV radiation fields which will tend to shrink the molecular regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation